Enthalpy Relaxation Rate of Poly(ethylene terephthalate) During Isothermal Crystallization - Li, Yibao (Asian Journal of Chemistry, 2014)
Isothermal crystallization behaviour of poly(ethylene terephthalate) (PET) from its melt were studied from the viewpoint of enthalpy relaxation rate (rh). The ratios of rh and relative crystallization rate (rc) are constant and their trends are the same during the whole crystallization. There is one relative degree of crystallinity (Xc) and time critical point (tc) at which the trend of rh increasing ended and it began decreasing. The values of degree of crystallinity, time critical point and enthalpy relaxation rates at 0 and Xc were figured out directly from the curve of enthalpy relaxation rate. It is provided new angle to insight crystallization process of polymeric melt.